Emission implications of electric vehicles in Japan considering energy structure transition and penetration uncertainty. (20th January 2021) - Xue, Mianqiang; Lin, Bin-Le; Tsunemi, Kiyotaka
Abstract: Vehicle electrification represents a promising solution to address the challenges of energy security and sustainable mobility. The environmental performance of electric vehicles is heavily dependent on the energy structure which is undergoing a profound transition. Moreover, the deployment of electric vehicles is critically affected by policies. In this context, this study investigated the impact of energy structure transition and penetration uncertainty on emissions of electric vehicles in Japan from 2000 to 2030. The results suggested that the greenhouse gas and reactive nitrogen were mitigated for both energy sources of electricity mix transition and ammonia energy carrier compared with the baseline. Trade-off between the electricity mix transition and ammonia energy carrier scenarios was observed. Specifically, the electricity mix transition results demonstrated a more significant emission reduction of reactive nitrogen, while an ammonia energy carrier led to a more significant emission reduction of greenhouse gas. Finally, key policy implications were summarized by providing insights into energy portfolio planning and electric vehicle deployment from the perspective of climate change mitigation and sustainable reactive nitrogen management. Highlights: Modeled penetration and energy structure transition for electric vehicles. Electricity mix transition led to more reactive nitrogen emission reduction. Ammonia energy carrier resulted in more greenhouse gas emission reduction. Implications were discussed providing insights into policy making.